2023
DOI: 10.1111/jvim.16615
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into an outbreak of pancytopenia in cats in the United Kingdom

Abstract: Background In spring 2021 increasing numbers of cats presenting with severe pancytopenia were noted in United Kingdom (UK). Objective To describe process and outcome of the investigation performed into the outbreak of pancytopenia in cats. Animals Five hundred and eighty client owned cats that presented with severe bi‐ or pancytopenia of unknown cause. Methods Real‐time data collection was performed by an online registration forum available to all veterinary surgeons in UK. Data collected included demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…Case fatality rate in this study was higher compared to the case fatality rate reported for the overall affected cohort 1 . This is thought to be due to 2 main factors.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…Case fatality rate in this study was higher compared to the case fatality rate reported for the overall affected cohort 1 . This is thought to be due to 2 main factors.…”
Section: Discussioncontrasting
confidence: 74%
“…This is thought to be due to 2 main factors. One, the reported case fatality rate for the overall affected cohort is likely an underestimation due to the nature of reporting and capture of data (“1 moment only”) in that study and also due to the fact that it is very likely that not all affected cats were registered on our data base 1 . In contrast, the case fatality rate reported here is likely an overestimation, as availability of bone marrow examinations results was an inclusion criterion.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations